PEMETAN SEBARAN DAN ANALISIS KEBUTUHAN GURU SMA NEGERI DI WILAYAH KOTA PADANG - 22, azriandi; Ernawati, Ernawati (JURNAL BUANA, 2023)
This study aims to calculate the needs of geography teachers, find out the distribution of geography teachers and the suitability of the qualifications of geography teachers with their educational background and map the distribution of needs for geography teachers at high school in the city of Padang. This research uses descriptive qualitative method. Data was collected by means of observation, interviews and documentation. Data analysis is by using maps, calculations using formulas and data descriptions. The results of this study (1) from the calculation of teacher needs, it is known that the geography teachers needed are 37 people while the existing teachers are 40 people, the teacher needs are categorized as excessive. (2) for the distribution of geography teachers at SMA in the city of swords has been categorized evenly because the number of teachers in each school has been fulfilled (3) Relevance of the educational background of geography teachers in SMA Negeri the number of geography teachers who are in accordance with the S1 background of geography education is 39 people or 97.5%, while those who are not in accordance with the educational background are 1 teachers or 2.5%.